2018
DOI: 10.5539/jas.v10n12p493
|View full text |Cite
|
Sign up to set email alerts
|

Substrates and Temperatures in the Germination of Hibiscus sabdariffa L. Seeds

Abstract: Vegetable biodiversity in Brazil accounts for almost 67% of the plants on the planet, which are part of studies with focus on determinants of food security and access to adequate and healthy food, while preserving natural resources. Studies indicate that Hibiscus sabdariffa L. is one of the most studied unconventional food crops because of its nutraceutical quality as antioxidant and prevention of hypertension and cancer. Although relevant, substrate and temperature information for seedling production of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
2
0
0
1
Order By: Relevance
“…Our results showed that the T b , T opt , and T max for H. sabdariffa germination were 5, 30, and 40 • C, respectively. These temperatures for H. sabdariffa seed germination are similar to those recorded by other authors (4.4, 29.30, and 50 • C, respectively) [63]. Similar findings were reported for Haloxylon aphyllum, Bouteloua curtipendula, and Calotropis procera [39,64].…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that the T b , T opt , and T max for H. sabdariffa germination were 5, 30, and 40 • C, respectively. These temperatures for H. sabdariffa seed germination are similar to those recorded by other authors (4.4, 29.30, and 50 • C, respectively) [63]. Similar findings were reported for Haloxylon aphyllum, Bouteloua curtipendula, and Calotropis procera [39,64].…”
Section: Discussionsupporting
confidence: 91%
“…This substrate has physicochemical characteristics that favor the emergence and development of seedlings, such as aeration, water retention and seed distribution. The efficiency of this substrate in the germination uniformity was also observed in other studies with seeds of Hibiscus sabdariffa [21] and Amburana cearensis [22]. However, the treatments with the lowest PCE values may have been characterized by low substrate moisture, making seed swelling difficult [17].…”
Section: Discussionsupporting
confidence: 65%
“…Studi dapat dilakukan pada tingkat perkecambahan benih atau fase bibit. Studi cekaman salinitas telah dilakukan di tingkat rumah kaca dengan pemberian asam salisilat dan gibrellin (GA3) (Novita et al, 2015), sedangkan kombinasi suhu dan substrat dipelajari untuk menghasilkan kondisi perkecambahan dan vigor terbaik (Gomes et al, 2018).…”
Section: Pendahuluanunclassified